Effect of iodine nutritional status on the recurrence of hyperthyroidism and antithyroid drug efficacy in adult patients with Graves’ disease: a systemic review - Xie, Qingxing; Zhang, Xinyi; Ma, Jinfang; Lu, Xi; Zhang, Yuwei; Tong, Nanwei (Frontiers in Endocrinology, 2023)
Aim To probe the appropriate iodine nutritional status for patients with Graves’disease (GD) hyperthyroidism and on antithyroid drugs (ATD) or after drugwithdrawal. Method Studies were retrieved from three databases (Embase, Medline, and Cochrane Library) and were screened and evaluated using predefined criteria. The risk of bias of each trial was assessed using a tool from Cochrane. The iodine nutritional status of the subjects was redefined according to the World Health Organization (WHO) criteria and classified as insufficient/adequate/above requirements/excessive iodine intake. Result Two randomized controlled trials (RCTs) and 3 observational studies were selected from the 376 retrieved papers, which had different degrees of risk of bias in study design. The heterogeneity among them prevented us from further synthesizing effect indicators and subsequent statistical analyses. Two RCTs with high quality showed that insufficient or above requirements iodine intake was detrimental for ATD-treated GD patients; adequate iodine intake was associated with a lower risk of recurrence and better efficacy in controlling thyrotoxicosis. It could be speculated from three low-quality observational studies that excessive iodine intake may be associated with higher (or similar) recurrence rates and lower remission rates compared to above requirements iodine intake in these patients, but none of them could answer the question of the effect of insufficient or adequate iodine intake on this issue. Conclusion Although the available evidence is suboptimal, this systematic review tentatively suggests that in adult patients with GD hyperthyroidism receiving ATDs and according to WHO criteria for iodine nutritional status, adequate iodine intake is associated with a lower recurrence rate, a higher remission rate and a better efficacy to control thyrotoxicosis than insufficient, above requirement, or excessive iodine intake. Future RCTs with large samples are expected to elucidate the actual impact of different iodine nutritional statuses on the recurrence rate of hyperthyroidism and the efficacy of ATD to control thyrotoxicosis in these patients. Systematic review registration identifier CRD42022359451.